Mental health and life satisfaction in East and West Germany: Effects of generation and migration of citizens - Beutel, Manfred E.; Braunheim, Lisa; Heller, Ayline; Schmutzer, Gabriele; Decker, Oliver; Brähler, Elmar (Frontiers in Public Health, 2022)
Objective The reunification of Germany after the separation between 1949 and 1990 has offered a unique chance of studying the impact of socialization, political transformation, and migration on mental health. The purpose of this article was to compare mental distress, resources, and life satisfaction (1) between residents of East and West Germany and migrants who have fled from East to West Germany before reunification and (2) between three generations. Methods We assessed anxiety, depression, resilience, self-esteem, and life satisfaction, comparing groups based on their residency and migration, as well as three different birth cohorts. Using a representative survey of 2006, analyses of variance show the differences between these groups. Based on a representative survey (N = 4,530), the effects of gender (53.6% women), residency/migration (74.4% grown up in the West, 20.4% in the East, 5.3% migrants from the East to the West) from three generations (32% born until 1945, 39% until 1967, and 29% to 1989), and positive and negative mental health indicators were analyzed. Results Women reported higher distress and lower resilience. Residents of the Western states reported the lowest burden of distress (depressive and anxiety symptoms) and the highest overall life satisfaction, exceeding residents from the Eastern states and migrants from the Eastern to the Western states. Migrants from the Eastern to the Western states, however, reported the lowest resilience and self-esteem. They reported lower satisfaction with income, living conditions (compared to the Western residents), and the lowest levels of satisfaction with family (compared to East and West). Conclusion Overall, our data point to inequalities between the Eastern and Western states regarding mental health 16 years after reunification favoring the residents of the Western states by lower distress and life satisfaction. Our data attest to the stresses and adjustments associated with migration from the Eastern to the Western states before reunification. A lower level of mental health and life satisfaction in the oldest generation may be related to the sequelae of World War II and also to aging.